Poor Maternal Heath Care in Rural Districts: An Attempt to Identify High Priority Districts of Bihar, India - Kishor P Brahmapurkar (Medsci Publications, 2017)
Background: As per NFHS-4, the percentage of mothers who had full antenatal care was lowest, 03 % in rural Bihar compared to all other states. So, the present study was the analysis of districts for the differences among factors related to the maternal health care with the objective to identify high priority districts among total 38 districts in Bihar. Materials and Methods: The study was carried out from the data of 38 districts of Bihar available from NFHS-4. High priority districts were included if the districts had full ANC below 03 % and had three or more than three favorable/unfavorable attributes below/above the findings for rural Bihar respectively . Results: Out of 38 districts 14 high priority districts were identified. 5 districts in Tirhut, all districts in Purnia and 2 districts in Munger Division were with high women's illiteracy and high percentage of child marriages in women and higher adolescent pregnancy. Conclusions: Rural Bihar had poor maternal health care with 14 high priority districts which needs corrective measures to improve. Sarva Shiksha Abhiyan (SSA) needs to be properly implemented to improve educational status of women. There is need for stern application of Prohibition of Child Marriage Act, 2006.